Controlling the Hierarchical Assembly of π‐Conjugated Oligoelectrolytes. Issue 16 (19th July 2018) - Zheng, Tingting; Feng, Huanhuan; van den Broek, Johanna M.; Rahimi, Khosrow; Kuehne, Alexander J. C.; de Vries, Renko; Sprakel, Joris
Abstract: Here, a means of controlling the assembly pathways of p‐conjugated oligoelectrolytes into supramolecular fibers and microtubes is presented, and it is shown how the addition of small end‐caps to well‐defined and pH‐responsive conjugated oligomers can alter the balance between repulsive and attractive supramolecular forces and enables control of the morphology of the hierarchical assembly process. The assembly stages from nuclei to protofibersare evidenced and a hypothesis on the mechanism of microtubes formation using a combination of analytical methods is provided, revealing different degrees of order at different scales along the structural hierarchy. Abstract : A strategy to control the assembly pathways of p‐conjugated oligoelectrolytes into supramolecular fibers and microtubes by altering the balance between repulsive and attractive supramolecular forces is presented . The assembly stages from nuclei to protofibers to microtubes are revealed, as well as different degrees of order at different scales along the structural hierarchy.